KONSTRUKSI EPISTEMOLOGI PENDIDIKAN ISLAM (Studi atas Pemikiran Kependidikan Prof. H. M. Arifin, M. Ed) - Abdul Ghofur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Epistemology of Islamic education is the object of knowledge, how to acquire knowledge and how to measure whether or not the knowledge related to the formation of personality, character, develop nature and all of human potential to the maximum to become good Muslims, have the mindset of a logical-critical, faithful, devoted, useful for themselves and their environment, and can achieve happiness in this world and in the hereafter in accordance with Islamic teachings. While Prof. H. M. Muzayin Arifin, M.Ed. epistemology of Islamic Education establish the truth of knowledge by measuring this knowledge by using Scientific through models of educational research that is based on Islamic values.